The impact of dietary sodium intake on sweat sodium concentration in response to endurance exercise: a systematic review - McCubbin, A. J.; Costa, R. J. S. (International Journal of Sports Science, 2018)
The collection, processing, and analysis of sweat samples to determine sodium losses during endurance exercise is common amongst sports and exercise nutrition practitioners, and necessary for researchers investigating sodium losses and replacement strategies. Several factors influence sweat sodium concentration ([Na+]) that need to be controlled or considered when interpreting results. Dietary sodium intake in the days preceding exercise is one factor that may influence sweat [Na+]. A systematic review was undertaking using six databases (CINAHL, Embase, Medline Ovid, Scopus, SPORTDiscus, and Web of Science) to determine the impact of dietary sodium intake on sweat [Na+] in response to endurance exercise. Six papers met the inclusion criteria. They varied in the level of sodium intake (+] due to diet, two showed no significant difference, and two were not analysed statistically. No relationship was found across studies comparing the difference in sodium intake between interventions and sweat [Na+]. Several limitations were identified, including lack of validation of the intervention, collecting regional sweat samples from limited sites or averaging results across sites or collection days, and lack of statistical analysis. It is concluded that the impact of dietary sodium intake on sweat [Na+] in response to endurance exercise remains uncertain, however the review provides useful insights into the optimal study design for future research in this area.